Analysis Of Financial Literacy: Case Study On Vulnerable Youth In Yogyakarta - Abbas, Elvina Nabilah; Wiranatakusuma, Dimas Bagus; Ardyanti, Febby Ferlita (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
In Indonesia the rate of literacy and inclusion is still low and its significant with the condition of economics now. Young people as pillars of the future civilization still need learning skill for the future especially in Yogyakarta as the city of the student. This study aims to described financial literacy and factors that affecting financial literacy of vulnerable youth in Yogyakarta. This study was qualitative with interview as a method of data collection and descriptive as a data analysis technique. The interview was semi-structured and the interviewees were vulnerable youth in Yogyakarta with some requirements. This study found that financial literacy in vulnerable youth in Yogyakarta are in medium level. Next, for the data that that not all conditions experienced by a vulnerable youth affect their financial literacy. For everyone in any situation can now obtain proper financial literacy and for influencers present a lot of financial literacy content. The government should give the explanation that financial literacy is not difficult to obtain.